Influence of the Board of Commissioners, Ownership Concentration, Audit Committee Meetings, Risk Management Committee, Leverage on Disclosure of Company Risk Management (Case Study of Banking Companies Registered on the Indonesia Stock Exchange for the 20 - Yudi Partama Putra; Asri Riastuti; Furqonti Ranidiah; Hesti Setiorini (Penerbit Jurnal Indonesia, 2023)
The research objective was to determine the effect of the board of commissioners, concentration of ownership, audit committee meetings, risk management committee, leverage on disclosure of corporate risk management in Banking Companies Registered on the Indonesia Stock Exchange for the 2018-2021 period. This type of research is quantitative research, data collection method is done by using documentation. The samples in this study were 28 banking companies listed on the Indonesia Stock Exchange during the 2018-2021 period. The data analysis techniques in this study were multiple linear regression analysis, determination tests and hypothesis testing. The test results for the board of commissioners affect disclosure of corporate risk management in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period because a significant value of 0.011 is smaller than 0.05. Ownership concentration has no effect on disclosure of company risk management in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period because a significant value of 0.331 is greater than 0.05. Audit committee meetings have an effect on disclosure of company risk management in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period because a significant value of 0.032 is smaller than 0.05. The risk management committee has an effect on disclosure of company risk management in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period because a significant value of 0.008 is smaller than 0.05. Leverage has no effect on disclosure of company risk management in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period because a significant value of 0.856 is greater than 0.05.